New data on spiders (Arachnida: Araneae) of Iraqi Kurdistan, with new species and records - Zamani, Alireza; Khudhur, Farhad A.; Marusik, Yuri M. (Magnolia Press, 2025)
Based on a series of specimens collected between 2021 and 2023, this study presents new data on spiders of Iraqi Kurdistan. Despite the small size of the collection (i.e., 74 specimens), the material was found to include five species new to science, which are described and illustrated in this paper: Dysdera goyzha sp. n. (♂♀; Sulaymaniyah) [Dysderidae], D. kurdistanica sp. n. (♂; Sulaymaniyah) [Dysderidae], Palpimanus garmiyanus sp. n. (♂; Sulaymaniyah) [Palpimanidae], Tegenaria sorani sp. n. (♂; Erbil) [Agelenidae], and Zelotes hazarmerdensis sp. n. (♀; Sulaymaniyah) [Gnaphosidae]. Two families (Cheiracanthiidae; Zoropsidae), eleven genera (Agalenatea Archer, 1951 [Araneidae]; Cheiracanthium C.L. Koch, 1839 [Cheiracanthiidae]; Drassodes Westring, 1851 [Gnaphosidae]; Gibbaranea Archer, 1951 [Araneidae]; Mesiotelus Simon, 1897 [Liocranidae]; Micrommata Latreille, 1804 [Sparassidae]; Porrhoclubiona Lohmander, 1944 [Clubionidae]; Rhysodromus Schick, 1965 [Philodromidae]; Steatoda Sundevall, 1833 [Theridiidae]; Trochosa C.L. Koch, 1847 [Lycosidae]; Zoropsis Simon, 1878 [Zoropsidae]) and 18 species are recorded in Iraq for the first time, and five species are newly reported from the Kurdistan Region.